1998
DOI: 10.1021/ac970574v
|View full text |Cite
|
Sign up to set email alerts
|

A Graphite-Assisted Laser Desorption/Ionization Study of Light-Induced Aging in Triterpene Dammar and Mastic Varnishes

Abstract: The light-induced aging of natural triterpenes used in varnishes was studied using graphite-assisted laser desorption/ionization mass spectrometry. This method was found to be superior to conventional matrix-assisted laser desorption/ionization for these materials because of higher signal levels and less chemical noise from the matrix. The dammar and mastic raw materials were found to be partially oxidized compared to their nominal composition, with up to six oxygens incorporated. The light-induced aging proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 13 publications
0
76
0
Order By: Relevance
“…More recently, nanomaterials [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] such as carbon nanotubes (CNT), 33 porous silicon, 34 silylated porous silicones, 35,36 titania sol-gel thin film, 37,38 silicon nanoparticles 39 and gold nanoparticles [40][41][42][43][44] have received much attention for use in surface-assisted laser desoption/ionization mass spectrometry (SALDI-MS), which utilizes these inorganic matrixes, because of their high surface areas, simple sample-preparation techniques, and flexibility of sample deposition under different conditions. Early in 1988, Tanaka et al used for the first time 30-nm-diameter cobalt nanoparticles suspended in glycerol to analyze lysozyme and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, nanomaterials [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] such as carbon nanotubes (CNT), 33 porous silicon, 34 silylated porous silicones, 35,36 titania sol-gel thin film, 37,38 silicon nanoparticles 39 and gold nanoparticles [40][41][42][43][44] have received much attention for use in surface-assisted laser desoption/ionization mass spectrometry (SALDI-MS), which utilizes these inorganic matrixes, because of their high surface areas, simple sample-preparation techniques, and flexibility of sample deposition under different conditions. Early in 1988, Tanaka et al used for the first time 30-nm-diameter cobalt nanoparticles suspended in glycerol to analyze lysozyme and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Early in 1988, Tanaka et al used for the first time 30-nm-diameter cobalt nanoparticles suspended in glycerol to analyze lysozyme and synthetic polymers. 27 Graphite powder in glycerol is also used for SALDI-MS 45,46 and mass imaging. 47 McLean et al have recently demonstrated that size-selected Au nanoparticles (AuNPs) with 2 -10 nm diameters can be used in SALDI-MS under dry surface conditions for the detection of peptides, such as substance P and phosphopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to analyze small molecules with conventional matrix due to matrix ion interference. Recently, porous silicon [12][13][14][15], matrix with high molecular weight [16,17], surfactant-suppressed matrix [18], and inorganic materials [19][20][21] have been successfully employed in the analysis of small molecules. However, there are no reports about the analysis of nonpolar PAHs by MALDI-TOF due to their great difficulty in ionization, though metal-assisted LDI analysis of nonpolar polyethylene was reported [22].…”
mentioning
confidence: 99%
“…23 As a matter of fact, glycerol was used in the early mass spectrometric observation of proteins by Tanaka. 24 Direct use of graphite without a matrix was attempted by Zumbuhl et al 25 Kim and Kang performed LDI-TOF MS of 2000 Da polypropyleneglycol and 2500 Da polystyrene using a 2-mm-thick graphite plate without a matrix. 26 Kim et al obtained a detailed molecular weight distribution of poly(methylsilsesquioxane)s in the 100-1000 Da range by GPLDI-TOF MS. 16 As shown in Figure 6, it appears that a significant portion of folates in the human blood exist as oxidized folates.…”
Section: Resultsmentioning
confidence: 99%